Inner-biblical Quotations in Old Testament Narra-tives: Some Methodological Considerations (ex. 1 Sam 15:2 and Deut 25:17–19) - Vang, Carsten (Old Testament Essays, 2020)
In the study of inner-biblical quotations in Old Testament narrative literature, much insight can be gleaned from the scholarly endeavour in the last twenty years of defining and interpreting allusions and quotations in the prophetic literature. Author-intended quotations from a precursor text should be distinguished from stock phrases and the use of recurrent identical phrases. Among the viable criteria for discerning the direction of dependence in quotations, it is relevant to mention unfamiliar language usage in one part of the parallel, dependence on context, and signs of interpretation for rhetorical purposes. These criteria are used to test the case of the parallel locutions in Deut 25:17–19 and 1 Sam 15:2–3. The article also stresses the need for a thorough study of repeated phraseology in the narrative literature. https://doi.org/10.17159/2312-3621/2020/v33n3a9